Avaliação da contaminação no entorno de um aterro de resíduos sólidos urbanos com base em resultados de poços de monitoramento - Mondelli, Giulliana; Giacheti, Heraldo Luiz [UNESP]; Hamada, Jorge [UNESP] (FapUNIFESP (SciELO), 2016)
This paper presents the environmental monitoring of the groundwater surrounding the municipal solid waste disposal site from Bauru, São Paulo, Brazil. In parallel with the several surveys carried out at this site, between January 2003 and April 2008, fourteen monitoring wells were installed at different periods of the geoenvironmental site investigation, following the Brazilian standards valid at that time and the demands observed with the interpretation of the site investigation data, to confirm the local contamination. The samples were collected using bailer, after rains and drought periods each year. The results obtained over time are presented, for the following parameters: groundwater table, pH, electrical conductivity, Ca2+, Cl‑, total Fe, DQO, NH4+, Zn2+, Na+, K+, and the ratio BOD/COD. The results of the long period of monitoring allowed the analysis of each parameter compared with what was happening superficially on the landfill, as well as natural characteristics of the aquifer. It is concluded that the contamination plume varies according to the layout and characteristics of the disposed waste, which recovery and mitigation should occur with the closure of the landfill.
Assessment of the contamination on the surrounding of a municipal solid waste landfill based on monitoring wells data
Keywords: Contamination plume; Geoenvironmental site investigation; Groundwater; Municipal solid waste landfill